Pretreatment method for increasing contact angle of flexible graphite plate

The hydrophilic groups of the flexible graphite plate are removed by ultra-high temperature treatment or silane coupling agent treatment, and combined with multiple roller pressing and impregnation processes, the problem of insufficient hydrophobicity of the flexible graphite plate is solved, significantly improving the contact angle and reducing water blockage. The phenomenon has improved the performance of fuel cells.

CN119191876APending Publication Date: 2024-12-27SHENZHEN HYDROGEN BLUE TIMES POWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411310727.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The hydrophobicity of flexible graphite plates is insufficient, resulting in too low contact angles, causing water blockage and reducing fuel cell performance.

Method used

The expanded graphite is treated by ultra-high temperature treatment or using a silane coupling agent to remove hydrophilic groups on the surface, and combined with rolling, vacuum molding and vacuum pressurization impregnation processes, a flexible graphite plate with improved hydrophobicity is formed.

Benefits of technology

It significantly improves the contact angle of the flexible graphite plate, reduces the phenomenon of water blockage, and improves the performance and life of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191876A_ABST
    Figure CN119191876A_ABST
Patent Text Reader

Abstract

The invention provides a pretreatment method for increasing a contact angle of a flexible graphite plate. The pretreatment method comprises the following steps: treating expanded graphite to remove hydrophilic groups on the surface of the expanded graphite; rolling the treated expanded graphite to form a flexible graphite prefabricated slab; carrying out vacuum mould pressing on the graphite prefabricated plate to form a runner; and the formed graphite prefabricated plate is subjected to vacuum pressurization impregnation, and the impregnated graphite prefabricated plate is cleaned and dried to obtain the flexible graphite plate. The hydrophilic groups on the surface of the prepared flexible graphite plate are reduced, so that the hydrophobicity of the surface of the flexible graphite plate is improved, the contact angle is remarkably increased, water generated in the running process of a galvanic pile is discharged, the water plugging phenomenon is reduced, and the performance of the galvanic pile is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fuel cells, and in particular to a pre-treatment method for improving the contact angle of a flexible graphite plate. Background Art

[0002] As one of the key components of fuel cells, the performance of flexible graphite bipolar plates directly affects the efficiency and life of fuel cells. In proton exchange membrane fuel cells, bipolar plates not only play the role of conducting electrons, but also need to have good thermal management and water management capabilities. Therefore, improving the hydrophobicity of bipolar plates has become one of the key technologies to optimize fuel cell performance.

[0003] At present, the common method for preparing flexible graphite plates is to roll the expanded graphite into a prefabricated plate through multiple rollers, then make the flow channel through compression molding, and finally perform impregnation treatment. The commonly used impregnation liquid includes acrylic resin or epoxy system. However, due to the insufficient hydrophobicity of the graphite and resin material system itself, the contact angle of the prepared flexible graphite plate is only about 70-80°. During high-temperature operation, the contact angle of the bipolar plate will further decrease. Too low a contact angle will make it difficult to effectively discharge the water generated during the operation of the battery stack, which can easily cause water plugging and reduce the performance of the battery stack. The contact angle is a measure of the angle when the liquid contacts the solid surface. It is the angle between the tangent of a small bead of liquid formed by the liquid dripping on the solid surface and the solid surface. A lower contact angle leads to an increase in the diffusion area of ​​water on the plate surface, which is not conducive to the timely removal of water generated inside the battery stack, and may cause water plugging, thereby having a negative impact on the performance of the battery stack. The size of the angle directly reflects the wettability or hydrophobicity of the solid surface. Since there are many hydrophilic groups on the surface of the graphite plate, the hydrophobicity is insufficient, which makes the water generated during the operation of the fuel cell stack easily cause water blockage.

[0004] Therefore, it is necessary to provide a pretreatment method that can effectively reduce the hydrophilic groups on the surface of the flexible graphite plate and improve the contact angle of the hydrophobic flexible graphite plate. Summary of the invention

[0005] In view of this, it is necessary to provide a pretreatment method for effectively reducing the hydrophilic groups on the surface of the flexible graphite plate and improving the contact angle of the hydrophobic flexible graphite plate to solve the above problems.

[0006] The embodiment of the present application provides a pre-treatment method for improving the contact angle of a flexible graphite plate, the method comprising the steps of:

[0007] Treating expanded graphite to remove hydrophilic groups on its surface;

[0008] Rolling the processed expanded graphite to form a flexible graphite prefabricated plate;

[0009] vacuum molding the graphite prefabricated plate to form a flow channel;

[0010] The graphite preformed plate is impregnated under vacuum pressure, and the impregnated graphite preformed plate is cleaned and dried to obtain a flexible graphite plate.

[0011] In at least one embodiment of the present application, the step of "treating expanded graphite to remove hydrophilic groups on its surface" includes the steps of: placing the expanded graphite in a muffle furnace for ultra-high temperature treatment at 1500°C-3000°C; adding inert gas during the treatment to obtain treated expanded graphite.

[0012] In at least one embodiment of the present application, the step of "treating expanded graphite to remove hydrophilic groups on its surface" includes the steps of: weighing a silane coupling agent and preparing a modified solution for standby use; stirring the silane coupling agent and the modified solution to obtain a hydrolyzed silane coupling agent; stirring the hydrolyzed silane coupling agent and expanded graphite, and filtering and drying to obtain the treated expanded graphite.

[0013] In at least one embodiment of the present application, in the step of "subjecting the expanded graphite to ultra-high temperature treatment in a muffle furnace", the treatment time is 10 min-30 min.

[0014] In at least one embodiment of the present application, the modification solution is a mixture of anhydrous ethanol and deionized water.

[0015] In at least one embodiment of the present application, in the step of "weighing the silane coupling agent and preparing the modified solution", the silane coupling agent is weighed according to the mass fraction of the expanded graphite of 0.1%-30%, anhydrous ethanol is weighed according to the volume ratio of 60%-90%, and deionized water is weighed at 10%-40%.

[0016] In at least one embodiment of the present application, in the step of "stirring the silane coupling agent and the modified solution to obtain a hydrolyzed silane coupling agent", the rotation speed of stirring the silane coupling agent and the modified solution is 200-800 r / min, and the stirring time is 10 min-600 min.

[0017] In at least one embodiment of the present application, in the step of "stirring the hydrolyzed silane coupling agent and expanded graphite, and filtering and drying to obtain the treated expanded graphite", the time for stirring the hydrolyzed silane coupling agent and expanded graphite is 10min-600min, the drying temperature is 40°C-80°C, and the drying time is 24h-72h.

[0018] In at least one embodiment of the present application, in the step of "rolling the treated expanded graphite to form a flexible graphite preformed plate", the rolling method is a multi-pass roller, the thickness of the flexible graphite preformed plate is 1mm-10mm, and the density of the flexible graphite preformed plate is 0.1-0.3g / cm3.

[0019] In at least one embodiment of the present application, the silane coupling agent is any one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, or γ-methacryloxypropyltrimethoxysilane.

[0020] The above-mentioned pretreatment method for improving the contact angle of a flexible graphite plate improves the hydrophobicity of the material by reducing or removing the hydrophilic groups on the surface of the expanded graphite. The treated expanded graphite is then rolled, vacuum molded, vacuum pressurized, impregnated, cleaned and dried to finally form a flexible graphite plate. The hydrophilic groups on the surface of the manufactured flexible graphite plate are reduced, so that the hydrophobicity of the surface of the flexible graphite plate is improved, thereby significantly improving the contact angle, which is beneficial to discharge the water generated during the operation of the battery stack, reduce water blockage, and improve the performance of the battery stack. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a flowchart of a preparation process for a pretreatment method for improving the contact angle of a flexible graphite plate in this application. DETAILED DESCRIPTION

[0022] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments.

[0023] It should be noted that when a component is considered to be "connected" to another component, it may be directly connected to the other component or there may be a central component at the same time. When a component is considered to be "located on" another component, it may be directly located on the other component or there may be a central component at the same time. The terms "top", "bottom", "upper", "lower", "left", "right", "front", "back", and similar expressions used herein are for illustrative purposes only.

[0024] The embodiment of the present application provides a pre-treatment method for improving the contact angle of a flexible graphite plate, the method comprising the steps of:

[0025] Treating expanded graphite to remove hydrophilic groups on its surface;

[0026] Rolling the processed expanded graphite to form a flexible graphite prefabricated plate;

[0027] vacuum molding the graphite prefabricated plate to form a flow channel;

[0028] The graphite preformed plate is impregnated under vacuum pressure, and the impregnated graphite preformed plate is cleaned and dried to obtain a flexible graphite plate.

[0029] The above-mentioned pretreatment method for improving the contact angle of a flexible graphite plate improves the hydrophobicity of the material by reducing or removing the hydrophilic groups on the surface of the expanded graphite. The treated expanded graphite is then rolled, vacuum molded, vacuum pressurized, impregnated, cleaned and dried to finally form a flexible graphite plate. The hydrophilic groups on the surface of the manufactured flexible graphite plate are reduced, so that the hydrophobicity of the surface of the flexible graphite plate is improved, thereby significantly improving the contact angle, which is beneficial to discharge the water generated during the operation of the battery stack, reduce water blockage, and improve the performance of the battery stack.

[0030] Some embodiments of the present application are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0031] according to Figure 1 In an embodiment of the present application, a pre-treatment method for improving the contact angle of a flexible graphite plate is provided, the method comprising the steps of:

[0032] S100, treating expanded graphite to remove hydrophilic groups on its surface;

[0033] S200, rolling the expanded graphite to form a flexible graphite prefabricated plate;

[0034] S300, vacuum molding the graphite prefabricated plate to form a flow channel;

[0035] S400, vacuum pressurizing and impregnating the formed graphite preformed plate, and cleaning and drying the impregnated graphite preformed plate to obtain a flexible graphite plate.

[0036] Specifically, step S100: treating expanded graphite to remove hydrophilic groups on its surface in Example 1:

[0037] (1) The expanded graphite is placed in a muffle furnace for ultra-high temperature treatment at 1500-3000°C, the high temperature process is maintained for 10 min-30 min, and an inert gas is added to the treatment pot to obtain the treated expanded graphite.

[0038] The expanded graphite is evenly placed in a high temperature resistant container in the muffle furnace. The container material must be able to withstand high temperatures without affecting the experimental results, such as using a high-purity graphite crucible. The ultra-high temperature treatment temperature is 1500℃-3000℃, and the treatment time is 10min-30min. During the entire high temperature treatment process, an inert atmosphere (such as argon or nitrogen) must be used for protection to prevent the expanded graphite from reacting with oxygen at high temperatures and oxidizing or burning, thereby obtaining the treated expanded graphite.

[0039] Under ultra-high temperature conditions, the oxidized groups (such as hydroxyl, carboxyl, etc.) on the surface of expanded graphite will undergo thermal decomposition. These groups are unstable at high temperatures and easily decompose into water vapor and other gases, thereby detaching from the graphite surface. Among them, the decomposition of hydroxyl groups: hydroxyl groups (—OH) usually undergo dehydration reactions at high temperatures to generate water (H2O) and new carbon-carbon bonds. This not only reduces the hydrophilic groups on the surface of expanded graphite, but may also enhance the interaction between graphite sheets. Decomposition of carboxyl groups: carboxyl groups (—COOH) decompose at ultra-high temperatures to produce carbon dioxide (CO2) and water (H2O). This decomposition helps to reduce the hydrophilicity of the surface of expanded graphite and increase its hydrophobicity.

[0040] Embodiment 2:

[0041] (1) weighing a silane coupling agent according to the mass fraction of expanded graphite of 0.1%-30%, weighing anhydrous ethanol of 60%-90% by volume, and weighing a modified solution of deionized water of 10%-40% by volume for standby use;

[0042] (2) stirring the silane coupling agent and the modified solution at a rotation speed of 200-800 r / min for a stirring time of 10-600 min to obtain a hydrolyzed silane coupling agent;

[0043] (3) stirring the hydrolyzed silane coupling agent and expanded graphite for 10 min to 600 min, and filtering and drying for 24 to 72 h to obtain the treated expanded graphite.

[0044] Specifically, the prepared solution is stirred at a speed of 200-800 r / min at room temperature for 10-600 min, and after the silane coupling agent is completely hydrolyzed, the expanded graphite is added and stirred for 10-600 min, filtered, and the treated expanded graphite is dried at 40-80° C. for 24-72 h to obtain the treated expanded graphite powder.

[0045] Further, the silane coupling agent generally has a functional group that can react with an inorganic material (such as expanded graphite). During the stirring reaction, the silane coupling agent is first hydrolyzed in a mixed solvent of anhydrous ethanol and deionized water to form silanol (Si-OH), and then the hydroxyl (-OH) of the silane coupling agent reacts with the hydroxyl (-OH) on the surface of the expanded graphite to form a hydrogen bond, so that the hydrophilic group on the surface of the expanded graphite is reduced and the hydrophobicity is improved. The formation of hydrogen bonds reduces the number of hydroxyl groups on the surface of the expanded graphite. The hydroxyl groups on the expanded graphite are originally hydrophilic groups that can attract water molecules. Through the formation of hydrogen bonds, the hydrophilic groups are consumed, thereby reducing the surface energy of the material and improving its hydrophobicity.

[0046] Step S200: using the expanded graphite treated in any one of the methods of Embodiment 1 or Embodiment 2 as a raw material, and rolling the treated expanded graphite to form a flexible graphite prefabricated plate;

[0047] Step S200 specifically includes:

[0048] The processed expanded graphite is rolled through multiple rollers to form a flexible graphite prefabricated plate with a thickness of 1mm-10mm and a density of 0.1-0.3g / cm3.

[0049] Step S300: vacuum molding the graphite prefabricated plate to form a flow channel.

[0050] Step S400: vacuum-pressurize and impregnate the preformed graphite plate, and clean and dry the impregnated preformed graphite plate to obtain a flexible graphite plate.

[0051] Specifically, the flexible graphite plate is impregnated under vacuum pressure, and the excess impregnation resin is cleaned, and the impregnated graphite prefabricated plate is cured and dried in a water bath to finally form a flexible graphite plate. Commonly used impregnation liquids are acrylic resins or epoxy systems, etc. These impregnation liquids themselves have good chemical stability and mechanical properties. Adding these impregnation liquids to the graphite prefabricated plate is intended to improve the overall performance of the flexible graphite plate, such as increasing strength and improving conductivity, without negatively affecting its hydrophobicity.

[0052] In a specific embodiment, the silane coupling agent is any one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, or γ-methacryloxypropyltrimethoxysilane.

[0053] Specifically, any one of the silane coupling agents, such as γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, or γ-methacryloxypropyl trimethoxysilane, is selected for the reaction. KH550 (γ-aminopropyl triethoxysilane) has an amino group (-NH2) and a triethoxysilane group. As an active group, the amino group can react with a variety of organic compounds, such as epoxy resins, polyurethanes, etc. On the surface of expanded graphite, KH550 can react with the hydroxyl groups on the graphite surface through its triethoxysilane part, thereby introducing amino functional groups and improving the adhesion with other polymer materials.

[0054] KH560 (γ-glycidyloxypropyltrimethoxysilane), KH560 contains a glycidyl ether group and a trimethoxysilane group. The glycidyl ether group has high reactivity and can react with a variety of compounds such as amines, acids and epoxides. In the application of expanded graphite, the trimethoxysilane of KH560 can react with the hydroxyl groups on the graphite surface, and the glycidyl ether group can provide additional reaction sites for further chemical modification or cross-linking.

[0055] KH570 (γ-methacryloxypropyltrimethoxysilane), KH570 has a methacryloxy group and a trimethoxysilane group. The methacryloxy group is an unsaturated ester that can participate in free radical polymerization. On the surface of expanded graphite, KH570 interacts with the graphite surface through its trimethoxysilane part, while the methacryloxy group can serve as a site for free radical polymerization and is used to graft polymer chains, thereby forming a polymer layer on the graphite surface.

[0056] By this, the above-mentioned pretreatment method for improving the contact angle of the flexible graphite plate is provided, by reducing or removing the hydrophilic groups on the surface of the expanded graphite to improve the hydrophobicity of the material. The treated expanded graphite is then rolled, vacuum molded, vacuum pressurized, impregnated, cleaned and dried to finally make a flexible graphite plate. The hydrophilic groups on the surface of the manufactured flexible graphite plate are reduced, so that the hydrophobicity of the surface of the flexible graphite plate is improved, so that the contact angle is significantly improved, which is conducive to discharging the water generated during the operation of the battery stack, reducing water blockage, and improving the performance of the battery stack.

[0057] The above is only an implementation method of the present application. It should be pointed out that a person skilled in the art can make improvements without departing from the inventive concept of the present application, but these improvements are within the scope of protection of the present application.

Claims

1. A pretreatment method for improving the contact angle of a flexible graphite sheet, characterized in that: The method comprises the steps of: Treating expanded graphite to remove hydrophilic groups on its surface; Rolling the processed expanded graphite to form a flexible graphite prefabricated plate; vacuum molding the graphite prefabricated plate to form a flow channel; The graphite preformed plate is impregnated under vacuum pressure, and the impregnated graphite preformed plate is cleaned and dried to obtain a flexible graphite plate.

2. A pretreatment method for improving the contact angle of a flexible graphite sheet according to claim 1, characterized in that: The step of "treating expanded graphite to remove hydrophilic groups on its surface" comprises the steps of: Place the expanded graphite in a muffle furnace for ultra-high temperature treatment at 1500℃-3000℃; Inert gas is added during the treatment process to obtain treated expanded graphite.

3. A pretreatment method for improving the contact angle of a flexible graphite sheet according to claim 1, characterized in that: The step of "treating expanded graphite to remove hydrophilic groups on its surface" comprises the steps of: Weigh the silane coupling agent and prepare a modified solution for later use; stirring the silane coupling agent and the modified solution to obtain a hydrolyzed silane coupling agent; The hydrolyzed silane coupling agent and expanded graphite are stirred, and then filtered and dried to obtain the treated expanded graphite.

4. A pretreatment method for improving the contact angle of a flexible graphite sheet according to claim 2, characterized in that In the step of "subjecting the expanded graphite to an ultra-high temperature treatment in a muffle furnace", the treatment time is 10 min to 30 min.

5. A pre-treatment method for improving the contact angle of a flexible graphite sheet according to claim 3, characterized in that: The modified solution is a mixture of anhydrous ethanol and deionized water.

6. A pre-treatment method for improving the contact angle of a flexible graphite sheet according to claim 5, characterized in that: In the step of "weighing the silane coupling agent and preparing the modified solution", the silane coupling agent is weighed according to the mass fraction of the expanded graphite of 0.1%-30%, anhydrous ethanol is weighed according to the volume ratio of 60%-90%, and deionized water is weighed according to 10%-40%.

7. A pre-treatment method for improving the contact angle of a flexible graphite sheet according to claim 3, characterized in that: In the step of "stirring the silane coupling agent and the modified solution to obtain a hydrolyzed silane coupling agent", the rotation speed of stirring the silane coupling agent and the modified solution is 200r / min-800r / min, and the stirring time is 10min-600min.

8. A pre-treatment method for improving the contact angle of a flexible graphite sheet according to claim 3, characterized in that: In the step of "stirring the hydrolyzed silane coupling agent and expanded graphite, and filtering and drying to obtain the treated expanded graphite", the time for stirring the hydrolyzed silane coupling agent and expanded graphite is 10min-600min, the drying temperature is 40°C-80°C, and the drying time is 24h-72h.

9. A pre-treatment method for improving the contact angle of a flexible graphite sheet according to claim 1, characterized in that: In the step of "rolling the treated expanded graphite to form a flexible graphite prefabricated plate", the rolling method is a multi-pass roller, the thickness of the flexible graphite prefabricated plate is 1mm-10mm, and the density of the flexible graphite prefabricated plate is 0.1-0.3g / cm3.

10. A pre-treatment method for improving the contact angle of a flexible graphite sheet according to claim 3, characterized in that: The silane coupling agent is any one of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane and γ-methacryloxypropyl trimethoxysilane.